(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Addiction to psychoactive substances or other harmful habits is often linked to social, psychological, and economic issues, making social work a complex field that provides emotional, informational, and practical support. This article examines social work practices in assisting individuals facing challenges, highlighting key professional difficulties such as stigma, lack of motivation, limited resources, and emotional burnout. The analysis of social workers' experiences in working with individuals struggling with alcohol addiction highlights the key challenges they encounter. Many clients enter treatment not by personal choice but due to external pressures, frequently exhibit skepticism and defensiveness, refusing help or denying their problems. Possible solutions include interdisciplinary collaboration, innovative working methods, and improved accessibility of social services. Based on practical examples and scientific research, the article identifies the most effective strategies that help social workers address addiction-related issues more efficiently and promote sustainable rehabilitation and reintegration. Social workers play a crucial role in guiding clients toward self-awareness, recognizing the need for change, and preparing them for recovery. However, the clients' motivation and willingness to cooperate remain essential factors for achieving lasting positive outcomes